A Study and Assessment of the Status of Energy Efficiency and Conservation at School Buildings - Ragab, Karim Mohamed (2022)
The building sector consumes a significant portion of global energy use. In this regard, this work was undertaken to study the status of energy efficiency and conservation at a large school building in the northern part of United Arab Emirates (UAE). The annual electrical consumption at the school was analyzed and an awareness survey among the students and teachers was conducted to measure the level of awareness as well as to assess the current energy consumption practices. In order to identify energy saving opportunities, an energy audit was carried out wherein the school energy consuming systems, particularly the lighting and air-conditioning systems, were assessed. Furthermore, thermography scanning of the school building envelope was conducted to examine the building insulation and identify air leakage locations. The building electricity supply and distribution systems were assessed using power analyzer and thermography devices. The energy conservation measures identified include removing the extra lighting, installing motion sensors in classrooms and labs, as well as integrating a Networked Optimization Software with the current HVAC (heating, ventilating and air conditioning) system. The methodology consists of seven fundamental steps: (1) case study data collection (analysis of buildings and utility data); (2) survey of real operation conditions; (3) understanding of building behavior; (4) analysis of energy conservation measures; (5) estimation of energy-saving potential; (6) economic assessment; and (7) proposing Energy Conservation Measures (ECMs). In this regard, the school energy consuming systems (lighting, building envelope, and air conditioning (AC)) were examined to identify possible ways to reduce the school energy consumption. The results indicate that the cost of installing motion sensors in classrooms, and labs is approximately AED 20,000 (United Arab Emirates Dirham), which yields an annual energy saving of AED 93,691. Furthermore, with all energy saving measures, a total annual saving of AED 364,000 is anticipated, which is approximately 16% of the annual electricity bill.